Frequency of malignant biliary strictures in Upper Egypt: a pilot study - Adnan A Mohamed; Ahmed M Ali; Mahmoud R Shehata; Wael A Elsewify; Salah Maklad (SpringerOpen, 2019)
Background and aim Biliary strictures are challenging clinical condition for gastroenterologists, radiologists, and surgical specialists. We aimed to find out the frequency of malignant biliary strictures in our institutions. Patients and methods This prospective study included 44 patients with biliary strictures who had undergone endoscopic retrograde cholangiopancreatography (ERCP) and magnetic resonance cholangiopancreatography (MRCP) in Aswan and Assiut University Hospitals. Results Thirty two patients (72.7%) had malignant strictures where distal stricture was the most frequent (68.8%) followed by hilar (25%) then mid and long segment strictures (3.1% each). Conclusion The vast majority of indeterminate biliary strictures are malignant (72.7%), so all indeterminate bile duct strictures in patients with obstructive jaundice should be considered malignant unless a benign etiology is definitively identifiable.